Analysis and Comparison of Color Features for Content Based Image Retrieval - Lande, Milind Vijayrao; PraveenBhanodiya, Prof.; Jain, Mr. Pritesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2005)
Creation of a content-based image retrieval system implies solving a number of difficult problems, including analysis of low-level image features and construction of feature vectors, multidimensional indexing, design of user interface, and data visualization. Color is one of the important features used in CBIR systems. The methods of characterizing color fall into two major categories:Â Histograms and Statistical. An experimental comparison of a number of different color features for content-based image retrieval presented in these paper. The primary goal is to determine which color feature is most efficient in representing the spatial distribution of images. In this paper, we analyze and evaluate both Statistical and Structural color features. For the experiments, publicly available image databases are used. Analysis and comparison of individual color features are presented